PELATIHAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS APLIKASI MYOB SEBAGAI UPAYA PENINGKATAN KOMPETENSI SISWA SMK KARYA NASIONAL KUNINGAN - Dendi Purnama; Amir Hamzah (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Competency improvement is very necessary for SMK students for accounting majors in preparing financial statements based on the MYOB application. To improve these competencies, training is needed to hone students' skills in preparing financial statements based on the MYOB application.  The purpose of this service activity is to improve the competence of SMK Karya Nasional students in preparing financial statements based on the MYOB application. General output of the training conducted to students of SMK Karya Nasional Kuningan in improving skills and competencies in the preparation of financial statements based on the MYOB-19 application as a provision to face accounting competency tests and the world of work. Participants who attended this activity were 30 people consisting of students majoring in Accounting at SMK Karya Nasional. The methods used in the implementation of service are training using technical information presentation and simulation methods as well as mentoring with individual and classical approaches. The service will be held on August 22, 2023. The results of this activity improve the skills of grade XI students majoring in accounting at SMK Karya Nasional to compile financial statements using the MYOB application. This is evidenced by their ability to enter transactions into the MYOB application